Mi árbol preferido - Küstermann, Alexis; Vecchio, Jorge; Hernández, Horacio; Shinjo, Elsa; Cuervo, Marina; Bottazzini, Constanza; Sánchez, Andrea; Mérida, Emilse; Hortiguera, Enrique; Di Giacomo, Gustavo (Revista Aves Argentinas, 2001)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).